Preparation method and application of cerium dioxide nanoparticles / nickel-iron bimetallic phosphide / nickel foam composite electrode
By preparing ceria nanoparticles/nickel iron bimetallic phosphide/foam nickel composite electrode, the problem of insufficient stability and activity of transition metal phosphide in catalytic oxygen precipitation reaction is solved, and the catalytic performance of the oxygen precipitation reaction is achieved. Stability significantly improves the overall efficiency of energy storage and conversion devices.
Patent Information
- Application Number
- CN202210623730.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-06-02
AI Technical Summary
In the energy storage and conversion device, transition metal phosphides exhibit poor long-term stability and catalytic activity in the catalytic oxygen precipitation reaction, limiting the overall efficiency.
The preparation method of ceria nanoparticles/nickel iron bimetallic phosphide/foam nickel composite electrode is adopted. Through electrochemical deposition and low-temperature phosphating technology, a composite electrode with good conductivity and porous structure is formed, and ceria nanoparticles are introduced. The oxygen vacancies are defective and produce strong electron interactions with the nickel-iron bimetallic phosphide interface, improving catalytic activity.
Excellent catalytic performance of oxygen precipitation reaction is achieved, the stability of the catalyst and electron transport efficiency are improved, the overpotential and taffel slope are significantly reduced, and the service life of the electrode is extended.
Smart Images

Figure CN115094456B_ABST
Abstract
Description
Technical field:
[0001] The invention relates to a preparation method of a cerium dioxide nanoparticle / nickel-iron bimetallic phosphide / nickel foam composite electrode and application of the composite electrode as a working electrode in an oxygen evolution reaction. Background technology:
[0002] Electrocatalytic oxygen evolution reaction plays a vital role in many energy storage and conversion devices, such as electrolyzers, metal-air batteries, and renewable fuel cells. However, its slow kinetics has become a major bottleneck limiting the overall efficiency of energy storage and conversion. In recent years, transition metal phosphides have attracted widespread attention due to their high catalytic activity and good electrical conductivity. However, transition metal phosphides generally show poor long-term stability in the process of catalyzing oxygen evolution reaction, and their catalytic activity still needs to be further improved.
[0003] According to literature reports, oxygen vacancy engineering is an effective strategy to adjust the electronic structure of catalysts and the adsorption of reaction intermediates, thereby optimizing catalyst activity. As an important rare earth oxide, cerium dioxide retains a unique 4f layer electronic structure, and the cation can flexibly change between trivalent and tetravalent. This multivalent nature can introduce abundant oxygen vacancy defects and provide opportunities for strong electronic interactions at the interface of heterostructure hybrids, which is conducive to the formation of catalytic active sites and the improvement of intrinsic catalytic activity. Cerium dioxide has a unique oxygen storage capacity and can immediately absorb the oxygen generated during the oxygen evolution reaction, thereby promoting the reaction. Therefore, the composite of cerium dioxide and transition metal phosphides can effectively improve its catalytic activity. In addition, the preparation of self-supporting electrodes by directly growing catalytically active materials on highly conductive nickel foam substrates can effectively improve the stability of catalysts on the electrode surface and the electron transfer efficiency, and inhibit the agglomeration of active materials, while avoiding the introduction of conductive polymer binders, which is more conducive to the exposure of active sites. Summary of the invention:
[0004] The purpose of the present invention is to provide a preparation method and application of a cerium dioxide nanoparticle / nickel iron bimetallic phosphide / nickel foam composite electrode. The composite electrode is prepared by combining electrochemical deposition and low-temperature phosphating, wherein the nickel iron bimetallic phosphide nanosheets and the nickel foam substrate have good conductivity and porous structure, which is conducive to rapid electron transfer and material transport; ultra-small cerium dioxide nanoparticles can introduce abundant oxygen vacancy defects, which is conducive to the formation of catalytic active sites, and the interface between the cerium dioxide nanoparticles and the nickel iron bimetallic phosphide produces strong electronic interaction, which can improve its intrinsic catalytic activity; cerium dioxide has a unique oxygen storage capacity, which can immediately absorb the oxygen generated during the oxygen evolution reaction, thereby promoting the reaction. The composite electrode exhibits excellent catalytic performance as a working electrode for the oxygen evolution reaction and has good application prospects. The oxygen vacancy engineering regulation strategy proposed in the present invention can also be extended to the design of other catalysts, providing a new idea for the development of efficient and low-cost catalysts.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] The preparation method of the cerium dioxide nanoparticle / nickel-iron bimetallic phosphide / nickel foam composite electrode comprises the following steps:
[0007] a. Cleaning the nickel foam: first, soak the nickel foam in acetone for 10 to 20 minutes, rinse with deionized water, then soak it in 2 to 4M hydrochloric acid solution for 10 to 20 minutes, rinse with deionized water and ethanol, and then dry it in a vacuum drying oven;
[0008] b. Prepare nickel-iron layered double hydroxide on nickel foam by constant voltage deposition method, using a standard three-electrode system, with the treated nickel foam as the working electrode, Ag / AgCl as the reference electrode, and carbon rod as the counter electrode. The electrochemical deposition is carried out at a constant potential of -0.8 to 1.2 V (relative to the Ag / AgCl electrode), the electrolyte is a mixed solution of 10.2 to 11.4 mM Ni(NO3)2·6H2O and 0.8 to 1.6 mM FeCl2·4H2O, the temperature of the electrolyte is 20 to 30°C, and the deposition time is 400 to 800 s. Then, the prepared electrode is carefully rinsed with water and ethanol, and then kept in a vacuum drying oven at 40 to 80°C for 6 to 10 hours to obtain a NiFe LDH / NF electrode;
[0009] c. Cerium dioxide nanoparticles were loaded on the NiFe LDH / NF electrode by constant current deposition. A standard three-electrode system was used, with nickel-iron layered double hydroxide / nickel foam electrode, Ag / AgCl and Pt sheet as working electrode, reference electrode and counter electrode, respectively. The cerium dioxide nanoparticles were electrochemically deposited at 0.2-0.3 mA cm -2The deposition was carried out at a constant current density of , the electrolyte was a mixed solution of 1.6-2.4 mM Ce(NO3)3·6H2O and 8-12 mM NaCl, the electrolyte temperature was 20-30°C, and the deposition time was 400-800 s. Next, the prepared electrode was carefully rinsed with water and ethanol, and then dried in a vacuum drying oven at 40-80°C to obtain a CeO2 / NiFe LDH / NF electrode;
[0010] d. CeO2 / NiFeP / NF composite electrode was prepared by annealing. A porcelain boat containing 400-600 mg sodium hypophosphite and CeO2 / NiFe LDH / NF electrode was placed in the upstream and middle parts of the tube furnace, respectively. Then, the mixture was kept at 250-350°C for 1.5-2.5 h in an argon environment at a heating rate of 1-3°C min -1 , and naturally cool to room temperature to obtain the CeO2 / NiFeP / NF composite electrode.
[0011] In the step c, the deposition of CeO2 nanoparticles can not only introduce abundant oxygen vacancy defects, but also generate strong electronic interactions at the interface of the heterostructure hybrid, thereby facilitating the formation of catalytic active sites and improving the intrinsic catalytic activity.
[0012] In the step d, the reactant is subjected to phosphating treatment to convert NiFe LDH into NiFeP with better conductivity and form a porous structure, thereby promoting electron transfer and material transport.
[0013] The cerium dioxide nanoparticle / nickel-iron bimetallic phosphide / nickel foam composite electrode is directly used as a working electrode for electrochemical testing, comprising the following steps:
[0014] a. First, cut the CeO2 / NiFeP / NF composite electrode into 0.2-0.8cm 2 size;
[0015] b. The electrochemical test was carried out in a standard three-electrode test system, wherein the electrode prepared in step a was used as the working electrode, the carbon rod electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and a KOH solution with a concentration of 0.8 to 1.2 M was used as the electrolyte;
[0016] c. Electrochemical tests were performed on an Ivium-n-Stat electrochemical workstation. When conducting polarization curve tests, the potential scan range relative to the Hg / HgO electrode was 0-0.95 V and the scan rate was 1 mV s -1 The electrochemical impedance spectroscopy test was carried out at a constant voltage of 0.54 V relative to the Hg / HgO electrode, with a scanning frequency of 100 kHz to 0.1 Hz. The chronopotentiometry test was carried out at a current density of 50 mA cm-2 The experiment was carried out under the conditions of 400 hours;
[0017] d. The prepared CeO2 / NiFeP / NF was used as the working electrode for oxygen evolution reaction. When the current density was 10 mA cm -2 When the overpotential is only 188mV, the Tafel slope is 32mV dec -1 , which has obvious advantages over CeO2 / NiFe LDH / NF, NiFe LDH / NF and NF. And the potential of the composite electrode has almost no change after 400h of chronopotentiometry test.
[0018] The technical effects of the present invention are:
[0019] The CeO2 / NiFeP / NF composite electrode prepared by the present invention has good electrical conductivity and material transport capability. The deposition of CeO2 not only introduces abundant oxygen vacancy defects, but also provides an opportunity for strong electronic interaction between heterogeneous structure hybrid interfaces, which can promote the formation of catalytic active sites and improve the intrinsic catalytic activity of the catalyst, so that the composite electrode exhibits excellent catalytic performance in oxygen evolution reaction. Description of the drawings:
[0020] Figure 1 , polarization curves of different electrodes in Example 1 of the present invention.
[0021] Figure 2 , FESEM photograph of the NiFe LDH / NF composite material prepared in Example 1 of the present invention.
[0022] Figure 3 , FESEM photograph of the CeO2 / NiFe LDH / NF composite material prepared in Example 1 of the present invention.
[0023] Figure 4 , TEM photo of the NiFe LDH prepared in Example 1 of the present invention.
[0024] Figure 5 , TEM photograph of the CeO2 / NiFe LDH composite material prepared in Example 1 of the present invention.
[0025] Figure 6 , FESEM photograph of the CeO2 / NiFeP / NF composite material prepared in Example 1 of the present invention.
[0026] Figure 7 , TEM photograph of the CeO2 / NiFeP composite material prepared in Example 1 of the present invention (the inset is a histogram of the particle size distribution of CeO2 nanoparticles).
[0027] Figure 8 , HRTEM photograph of the CeO2 / NiFeP composite material prepared in Example 1 of the present invention.
[0028] Fig. 9 , XRD patterns of NiFe LDH / NF and CeO2 / NiFe LDH / NF composite materials prepared in Example 1 of the present invention.
[0029] Fig.10 , XRD spectrum of the CeO2 / NiFeP composite material prepared in Example 1 of the present invention.
[0030] Fig.11 , BET spectrum of the CeO2 / NiFeP composite material prepared in Example 1 of the present invention (the inset is the pore size distribution diagram of the CeO2 / NiFeP composite material).
[0031] Fig.12 , XPS spectrum of the CeO2 / NiFeP / NF composite material prepared in Example 1 of the present invention.
[0032] Fig.13 , High-resolution XPS spectrum of the Ni 2p region of the CeO2 / NiFeP / NF composite material prepared in Example 1 of the present invention.
[0033] Fig.14 , High-resolution XPS spectrum of the Fe 2p region of the CeO2 / NiFeP / NF composite material prepared in Example 1 of the present invention.
[0034] Fig.15 , High-resolution XPS spectrum in the P 2p region of the CeO2 / NiFeP / NF composite material prepared in Example 1 of the present invention.
[0035] Fig.16 , High-resolution XPS spectrum of Ce 3d region of CeO2 / NiFeP / NF composite material prepared in Example 1 of the present invention.
[0036] Fig.17 , High-resolution XPS spectrum in the O1s region of the CeO2 / NiFeP / NF composite material prepared in Example 1 of the present invention.
[0037] Fig.18 , Tafel curves of different electrodes in Example 1 of the present invention.
[0038] Fig.19 , electrochemical impedance spectra of different electrodes in Example 1 of the present invention.
[0039] Fig. 20, the chronopotentiometry curve of the CeO2 / NiFeP / NF composite electrode prepared in Example 1 of the present invention (the inset is a FESEM photograph of the CeO2 / NiFeP / NF composite electrode after 400h stability test).
[0040] Fig.21 , FESEM photograph of the CeO2 / NiFe LDH / NF composite material prepared in Example 2 of the present invention.
[0041] Fig. 22 , FESEM photograph of the CeO2 / NiFe LDH / NF composite material prepared in Example 3 of the present invention. Specific implementation method:
[0042] The specific content and implementation methods of the present invention are further described in conjunction with the examples, however, the examples are only provided for illustration and cannot constitute a limitation on the technical solution of the present invention. The contents of Examples 2 and 3 of the present invention are similar to those of Example 1, and Example 1 is now described in detail.
[0043] Example 1
[0044] The preparation process and steps in this embodiment are as follows:
[0045] (1) Cleaning the nickel foam: first, soak the nickel foam in acetone for 15 min, rinse with deionized water, then soak in 3M hydrochloric acid solution for 15 min, rinse with deionized water and ethanol, and then dry in a vacuum drying oven;
[0046] (2) Nickel-iron layered double hydroxide was prepared on nickel foam by constant voltage deposition method. A standard three-electrode system was used, with the treated nickel foam as the working electrode, Ag / AgCl as the reference electrode, and carbon rod as the counter electrode. The electrochemical deposition was carried out at a constant potential of -1.0 V (relative to the Ag / AgCl electrode). The electrolyte was a mixed solution of 10.8 mM Ni(NO3)2·6H2O and 1.2 mM FeCl2·4H2O. The temperature of the electrolyte was 25°C, and the deposition time was 600 s. Then, the prepared electrode was carefully rinsed with water and ethanol, and then kept in a vacuum drying oven at 60°C for 8 h to obtain a NiFe LDH / NF electrode;
[0047] (3) Cerium dioxide nanoparticles were loaded on the NiFe LDH / NF electrode by constant current deposition. A standard three-electrode system was used, with nickel-iron layered double hydroxide / nickel foam electrode, Ag / AgCl and Pt sheet as working electrode, reference electrode and counter electrode, respectively. The cerium dioxide nanoparticles were electrochemically deposited at 0.25 mA cm -2The deposition was carried out at a constant current density of , the electrolyte was a mixed solution of 2mM Ce(NO3)3·6H2O and 10mM NaCl, the electrolyte temperature was 25°C, and the deposition time was 600s. Next, the prepared electrode was carefully rinsed with water and ethanol, and then dried in a vacuum drying oven at 60°C to obtain a CeO2 / NiFe LDH / NF electrode;
[0048] (4) CeO2 / NiFeP / NF composite electrode was prepared by annealing. A porcelain boat containing 500 mg sodium hypophosphite and CeO2 / NiFe LDH / NF electrode was placed in the upstream and middle parts of the tube furnace, respectively, and then kept at 300 °C for 2 h in an argon environment with a heating rate of 2 °C min -1 , and naturally cool to room temperature to obtain the CeO2 / NiFeP / NF composite electrode.
[0049] (5) Cut the CeO2 / NiFeP / NF composite electrode into 0.5 cm 2 The size of the electrode was directly used as the working electrode, the carbon rod electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and the KOH solution with a concentration of 1.0 M was used as the electrolyte to form a standard three-electrode system for electrochemical testing.
[0050] (6) The CeO2 / NiFeP / NF composite electrode was used as the working electrode to perform the test on an Ivium-n-Stat electrochemical workstation. When performing the polarization curve test, the potential scanning range relative to the Hg / HgO electrode was 0-0.95 V, and the scanning speed was 1 mV s -1 The electrochemical impedance spectroscopy test was carried out at a constant voltage of 0.54 V relative to the Hg / HgO electrode, with a scanning frequency of 100 kHz to 0.1 Hz. The chronopotentiometry test was carried out at a current density of 50 mA cm -2 The experiment was carried out under the conditions of 400 hours.
[0051] Morphology and structure characterization of CeO2 / NiFeP / NF composite electrode:
[0052] The surface morphology of different samples was characterized by field emission scanning electron microscopy (FESEM). Figure 2 and Figure 3 These are the FESEM photos of NiFeLDH / NF and CeO2 / NiFe LDH / NF composites. It can be seen that NiFe LDH nanosheets grow vertically on nickel foam. After the constant current electrodeposition process, many CeO2 nanoparticles are evenly loaded on the nanosheets. Figure 4 and Figure 5The transmission electron microscope (TEM) images of NiFe LDH and CeO2 / NiFe LDH respectively, more intuitively prove the successful loading of CeO2 nanoparticles. Figure 6 This is a FESEM photo of the CeO2 / NiFeP / NF composite electrode. After phosphating, CeO2 / NiFeP still maintains the morphology of nanosheets with an average thickness of about 10nm. These ultra-thin nanosheets are interconnected and form an open porous structure, which not only exposes abundant active sites but also accelerates material transport. Figure 7 This is a TEM photo of CeO2 / NiFeP composite material. CeO2 nanoparticles with an average particle size of only about 5nm are evenly distributed on NiFeP nanosheets. Figure 8 This is a high-resolution TEM (HRTEM) image of CeO2 / NiFeP composite material. The interplanar spacings of 0.203nm and 0.221nm correspond to the (201) and (111) planes of NiFeP, respectively, and 0.191nm, 0.271nm and 0.303nm correspond to the (220), (200) and (111) planes of CeO2, respectively. Fig. 9 Figure 2 shows the X-ray diffraction (XRD) patterns of NiFeLDH / NF and CeO2 / NiFe LDH / NF composites. The diffraction peaks at 10.3°, 21.7°, 34.5° and 60.7° correspond to the (003), (006), (012) and (110) crystal planes of NiFe LDH (JCPDS No.51-0463), respectively. The strong diffraction peaks at 47.3°, 54.2° and 74.7° correspond to the nickel foam substrate. After depositing CeO2, weaker diffraction peaks appear at 28.3° and 48.6°, corresponding to the (111) and (220) crystal planes of CeO2 (JCPDS No.34-0394). Fig.10 Figure 1 is the XRD spectrum of CeO2 / NiFeP composite material. The diffraction peaks at 30.5°, 31.8°, 40.8°, 44.6°, 47.3°, 54.2°, 54.9°, 66.2°, 72.7° and 74.7° correspond to the (110), (101), (111), (201), (210), (300), (211), (310), (311) and (400) crystal planes of NiFeP, which are basically consistent with Ni2P (JCPDS No.74-1385) and Fe2P (JCPDS No.51-0943). The characteristic peak of CeO2 does not appear in the spectrum, which may be due to the small size of CeO2 nanoparticles and poor crystallinity. Fig.11The N2 adsorption / desorption isotherms and pore size distribution of CeO2 / NiFeP composite materials. According to the Brunauer-Emmer-Teller (BET) model and the Barrett-Joyner-Halenda (BJH) method, the specific surface area of the composite material is 7m 2 g -1 The pore size distribution diagram shows that CeO2 / NiFeP composites contain both small (<10nm) and large mesopores (10-100nm). The smaller mesopores are mainly due to the shrinkage of the nanosheets during the phosphating process, while the larger mesopores are due to the overlap and cross-linking of the nanosheets. This porous structure is conducive to the penetration of electrolytes and the diffusion of gases, which can improve the catalytic performance of CeO2 / NiFeP / NF electrodes. Fig.12 This is the full XPS spectrum of the CeO2 / NiFeP / NF composite material. It can be seen that the composite material contains Ni, Fe, Ce, O, C and P elements, among which the presence of C is due to the inevitable carbon contamination of the sample when it is exposed to the air. Figures 13 to 17 High-resolution XPS spectra of Ni 2p, Fe 2p, P 2p, Ce 3d and O1s respectively. Fig.13 According to Ni 2p 3 / 2 The two characteristic peaks located at 855.8eV and 858.2eV indicate that Ni exists in the form of Ni 2+ and Ni 3+ .according to Fig.14 It can be seen that Fe is Fe 3+ exists in the form of. Fig.15 The characteristic peaks with binding energies of 129.2 eV and 132.8 eV correspond to the PM (M = Ni, Fe) bond and the PO bond, respectively. Fig.16 It can be seen that Ce in CeO2 / NiFeP / NF composites 3+ and Ce 4+ are coexistent, which may introduce abundant oxygen vacancy defects. Fig.17 This further confirms this view. Fig.17 The characteristic peaks at 529.3eV and 529.9eV correspond to the MO bond and the M-OH bond, respectively. The characteristic peak at 531.4eV is the binding energy site of the oxygen atoms around the oxygen vacancies. The appearance of this peak indicates that there are abundant oxygen vacancies in the CeO2 / NiFeP / NF composite material. The characteristic peak at 533.0eV corresponds to the water molecules adsorbed on the surface of the material.
[0053] Characterization of electrocatalytic performance of CeO2 / NiFeP / NF composite electrode at room temperature:
[0054] The electrochemical tests were performed using a standard three-electrode test system. Figure 1For different electrodes at 1mV s -1 Polarization curves at a scan rate of 10 mA cm -2 The minimum overpotential at the current density of 188 mV is shown, which is much lower than CeO2 / NiFe LDH / NF (215 mV), NiFe LDH / NF (225 mV) and NF (393 mV). Such excellent catalytic activity is due to the fact that the deposited CeO2 nanoparticles can introduce abundant oxygen vacancy defects and generate strong electronic interactions at the interface of heterostructure hybrids, which is conducive to the formation of catalytic active sites and the improvement of intrinsic catalytic activity. At the same time, the phosphating treatment converts the poorly conductive NiFe LDH into highly conductive NiFeP and forms a porous structure, which promotes electron transfer and material transport. Fig.18 The corresponding Tafel curves are shown in Figure 2. The Tafel slopes of CeO2 / NiFeP / NF, CeO2 / NiFe LDH / NF, NiFe LDH / NF and NF are 32, 44, 49 and 99 mV dec, respectively. -1 The CeO2 / NiFeP / NF composite electrode exhibits the smallest Tafel slope, indicating that it has the fastest reaction kinetics. Fig.19 The corresponding electrochemical impedance spectrum shows that the charge transfer resistance of CeO2 / NiFeP / NF is only 1.3Ω, which is much lower than CeO2 / NiFeLDH / NF (3.2Ω) and NiFe LDH / NF (5.8Ω). This indicates that the CeO2 / NiFeP / NF composite electrode has the fastest charge transfer kinetics, which is conducive to the improvement of catalytic activity. Fig. 20 The chronopotentiometry curve of CeO2 / NiFeP / NF composite electrode at 50 mA cm -2 At a current density of 1.5 Å, after 400 h of continuous testing, the potential of the composite electrode hardly increased. As shown in the inset, the CeO2 / NiFeP / NF composite electrode after the stability test still maintains the original nanosheet morphology without obvious collapse and agglomeration, indicating that the composite electrode has excellent stability. In summary, the CeO2 / NiFeP / NF composite electrode exhibits excellent OER catalytic performance. The reasons are as follows: the deposition of CeO2 nanoparticles can introduce abundant oxygen vacancy defects and generate strong electronic interactions at the interface formed with NiFeP, promoting the formation of catalytic active sites and the improvement of intrinsic catalytic activity; CeO2 has a unique oxygen storage capacity and can immediately absorb the oxygen generated during the OER process, thereby promoting the OER process; the high conductivity and porous structure of NiFeP nanosheets and nickel foam substrate are conducive to rapid electron transfer and material transport.
[0055] Example 2
[0056] The preparation process and steps in this embodiment are as follows:
[0057] (1) Cleaning the nickel foam: first, soak the nickel foam in acetone for 15 min, rinse with deionized water, then soak in 3M hydrochloric acid solution for 15 min, rinse with deionized water and ethanol, and then dry in a vacuum drying oven;
[0058] (2) Nickel-iron layered double hydroxide was prepared on nickel foam by constant voltage deposition method. A standard three-electrode system was used, with the treated nickel foam as the working electrode, Ag / AgCl as the reference electrode, and carbon rod as the counter electrode. The electrochemical deposition was carried out at a constant potential of -1.0 V (relative to the Ag / AgCl electrode). The electrolyte was a mixed solution of 10.8 mM Ni(NO3)2·6H2O and 1.2 mM FeCl2·4H2O. The temperature of the electrolyte was 25°C, and the deposition time was 600 s. Then, the prepared electrode was carefully rinsed with water and ethanol, and then kept in a vacuum drying oven at 60°C for 8 h to obtain a NiFe LDH / NF electrode;
[0059] (3) Cerium dioxide nanoparticles were loaded on the NiFe LDH / NF electrode by constant current deposition. A standard three-electrode system was used, with nickel-iron layered double hydroxide / nickel foam electrode, Ag / AgCl and Pt sheet as working electrode, reference electrode and counter electrode, respectively. The cerium dioxide nanoparticles were electrochemically deposited at 0.25 mA cm -2 The deposition was carried out at a constant current density of , the electrolyte was a mixed solution of 2mM Ce(NO3)3·6H2O and 10mM NaCl, the electrolyte temperature was 25°C, and the deposition time was 300s. Next, the prepared electrode was carefully rinsed with water and ethanol, and then dried in a vacuum oven at 60°C to obtain a CeO2 / NiFe LDH / NF electrode;
[0060] (4) CeO2 / NiFeP / NF composite electrode was prepared by annealing. A porcelain boat containing 500 mg sodium hypophosphite and CeO2 / NiFe LDH / NF electrode was placed in the upstream and middle parts of the tube furnace, respectively, and then kept at 300 °C for 2 h in an argon environment with a heating rate of 2 °C min -1 , and naturally cool to room temperature to obtain the CeO2 / NiFeP / NF composite electrode.
[0061] (5) Cut the CeO2 / NiFeP / NF composite electrode into 0.5 cm 2 The size of the electrode was directly used as the working electrode, the carbon rod electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and the KOH solution with a concentration of 1.0 M was used as the electrolyte to form a standard three-electrode system for electrochemical testing.
[0062] (6) The CeO2 / NiFeP / NF composite electrode was used as the working electrode to perform the test on an Ivium-n-Stat electrochemical workstation. When performing the polarization curve test, the potential scanning range relative to the Hg / HgO electrode was 0-0.95 V, and the scanning speed was 1 mV s -1 The electrochemical impedance spectroscopy test was carried out at a constant voltage of 0.54 V relative to the Hg / HgO electrode, with a scanning frequency of 100 kHz to 0.1 Hz. The chronopotentiometry test was carried out at a current density of 50 mA cm -2 The experiment was carried out under the conditions of 400 hours.
[0063] The FESEM image of the CeO2 / NiFe LDH / NF composite electrode prepared in this example is as follows: Fig.21 As shown in the figure, it can be seen that the composite electrode prepared in this embodiment has a similar morphology to the electrode prepared in Example 1, and both are uniformly loaded with CeO2 nanoparticles, which is beneficial to the improvement of catalytic performance.
[0064] Example 3
[0065] The preparation process and steps in this embodiment are as follows:
[0066] (1) Cleaning the nickel foam: first, soak the nickel foam in acetone for 15 min, rinse with deionized water, then soak in 3M hydrochloric acid solution for 15 min, rinse with deionized water and ethanol, and then dry in a vacuum drying oven;
[0067] (2) Nickel-iron layered double hydroxide was prepared on nickel foam by constant voltage deposition method. A standard three-electrode system was used, with the treated nickel foam as the working electrode, Ag / AgCl as the reference electrode, and carbon rod as the counter electrode. The electrochemical deposition was carried out at a constant potential of -1.0 V (relative to the Ag / AgCl electrode). The electrolyte was a mixed solution of 10.8 mM Ni(NO3)2·6H2O and 1.2 mM FeCl2·4H2O. The temperature of the electrolyte was 25°C, and the deposition time was 600 s. Then, the prepared electrode was carefully rinsed with water and ethanol, and then kept in a vacuum drying oven at 60°C for 8 h to obtain a NiFe LDH / NF electrode;
[0068] (3) Cerium dioxide nanoparticles were loaded on the NiFe LDH / NF electrode by constant current deposition. A standard three-electrode system was used, with nickel-iron layered double hydroxide / nickel foam electrode, Ag / AgCl and Pt sheet as working electrode, reference electrode and counter electrode, respectively. The cerium dioxide nanoparticles were electrochemically deposited at 0.25 mA cm -2The deposition was carried out at a constant current density of , the electrolyte was a mixed solution of 2mM Ce(NO3)3·6H2O and 10mM NaCl, the electrolyte temperature was 25°C, and the deposition time was 900s. Next, the prepared electrode was carefully rinsed with water and ethanol, and then dried in a vacuum drying oven at 60°C to obtain a CeO2 / NiFe LDH / NF electrode;
[0069] (4) CeO2 / NiFeP / NF composite electrode was prepared by annealing. A porcelain boat containing 500 mg sodium hypophosphite and CeO2 / NiFe LDH / NF electrode was placed in the upstream and middle parts of the tube furnace, respectively, and then kept at 300 °C for 2 h in an argon environment with a heating rate of 2 °C min -1 , and naturally cool to room temperature to obtain the CeO2 / NiFeP / NF composite electrode.
[0070] (5) Cut the CeO2 / NiFeP / NF composite electrode into 0.5 cm 2 The size of the electrode was directly used as the working electrode, the carbon rod electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and the KOH solution with a concentration of 1.0 M was used as the electrolyte to form a standard three-electrode system for electrochemical testing.
[0071] (6) The CeO2 / NiFeP / NF composite electrode was used as the working electrode to perform the test on an Ivium-n-Stat electrochemical workstation. When performing the polarization curve test, the potential scanning range relative to the Hg / HgO electrode was 0-0.95 V, and the scanning speed was 1 mV s -1 The electrochemical impedance spectroscopy test was carried out at a constant voltage of 0.54 V relative to the Hg / HgO electrode, with a scanning frequency of 100 kHz to 0.1 Hz. The chronopotentiometry test was carried out at a current density of 50 mA cm -2 The experiment was carried out under the conditions of 400 hours.
[0072] The FESEM image of the CeO2 / NiFe LDH / NF composite electrode prepared in this example is as follows: Fig. 22 As shown in the figure, it can be seen that the composite electrode prepared in this embodiment has a similar morphology to the electrodes prepared in Example 1 and Example 2, and both are uniformly loaded with CeO2 nanoparticles, which is beneficial to the improvement of catalytic performance. This also fully demonstrates that the application range of this experiment is relatively wide.
Claims
1. A method for preparing a cerium dioxide nanoparticle / nickel-iron bimetallic phosphide / nickel foam composite electrode, characterized in that: The following steps are involved: a. Clean the nickel foam. First, soak the nickel foam in acetone for 10-20 min, rinse with deionized water, then soak it in 2-4 M hydrochloric acid solution for 10-20 min, rinse with deionized water and ethanol, and then dry it in a vacuum drying oven; b. Prepare nickel-iron layered double hydroxide on nickel foam by constant voltage deposition method. A standard three-electrode system is used. The treated nickel foam is used as the working electrode, Ag / AgCl is used as the reference electrode, and the carbon rod is used as the counter electrode. The electrochemical deposition is carried out at a constant potential of -0.8~1.2 V relative to the Ag / AgCl electrode. The electrolyte is a mixed solution of 10.2~11.4 mM Ni(NO3)2∙6H2O and 0.8~1.6 mM FeCl2∙4H2O. The temperature of the electrolyte is 20~30 °C, and the deposition time is 400~800 s. Then, the prepared electrode is rinsed with water and ethanol, and then kept in a vacuum drying oven at 40~80 °C for 6~10 h to obtain a NiFe LDH / NF electrode. c. Cerium dioxide nanoparticles were loaded on the NiFe LDH / NF electrode by constant current deposition. A standard three-electrode system was used, with NiFe LDH / nickel foam electrode, Ag / AgCl and Pt sheet as working electrode, reference electrode and counter electrode, respectively. The electrochemical deposition was carried out at 0.2-0.3 mA cm -2 The deposition was carried out at a constant current density of 1.6-2.4 mM Ce(NO3)3∙6H2O and 8-12 mM NaCl in the electrolyte. The temperature of the electrolyte was 20-30°C. The deposition time was 400-800 s. Then, the prepared electrode was carefully rinsed with water and ethanol, and then dried in a vacuum oven at 40-80°C to obtain a CeO2 / NiFe LDH / NF electrode. d. CeO2 / NiFeP / NF composite electrode was prepared by annealing. A porcelain boat containing 400-600 mg sodium hypophosphite and CeO2 / NiFe LDH / NF electrode was placed in the upstream and middle parts of the tube furnace, respectively. The mixture was then heated at 250-350 °C for 1.5-2.5 h in an argon environment at a heating rate of 1-3 °C min -1 , and naturally cool to room temperature to obtain the CeO2 / NiFeP / NF composite electrode; e. In step c, abundant oxygen vacancy defects can be introduced and strong electronic interactions can be generated at the interface of heterostructure hybrids, thereby facilitating the formation of catalytic active sites and improving intrinsic catalytic activity; f. In step d, the reactant is subjected to phosphating treatment to convert NiFe LDH into NiFeP and form a porous structure, thereby promoting electron transfer and material transport; 2. The use of the cerium dioxide nanoparticles / nickel-iron bimetallic phosphide / nickel foam composite electrode prepared according to the method of claim 1, characterized in that: The composite electrode was directly used as a working electrode for electrochemical testing. −2 When the overpotential is only 188 mV, the Tafel slope is 32 mV dec. −1 , compared with CeO2 / NiFe LDH / NF, NiFe LDH / NF and NF, the composite electrode has obvious advantages, and the potential of the composite electrode has hardly changed after 400 h of chronopotentiometry test, showing excellent stability.
